2004
DOI: 10.3136/fstr.10.307
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ethanol in Improvement of Bacterial Cellulose Production: Analysis Using 13C-Labeled Carbon Sources

Abstract: We studied the role of ethanol in the improvement of bacterial cellulose (BC) production, primarily using 13C NMR. 13C-labeled BC was biosynthesized by Acetobacter xylinum ATCC 10245 using culture media containing D-(1-13C), (2-13C), and (6-13C)glucose. The introduction of (1-13C) ethanol was also investigated.Ethanol was not utilized as a carbon source for BC production, but was oxidized to acetic acid. The consumption rate of glucose and the extracellular conversion of glucose into gluconic acids were suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 16 publications
5
35
0
Order By: Relevance
“…This study also suggests that ethanol acts not as a substrate for BC biosynthesis but as an energy source for ATP generation in the viable cells, increasing BC production as a result. Similar results have been found in studies with G. hansenii, (Park et al 2003) and with A. xylinum ATCC 10245 (Yunoki et al 2004). In the latter report, the authors suggest that ethanol was not the carbon source for BC production and that the improvement was a consequence of ethanol suppressing the transformation of glucose in gluconic acids, a process that potentiates a more efficient polymerization of glucose into BC.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study also suggests that ethanol acts not as a substrate for BC biosynthesis but as an energy source for ATP generation in the viable cells, increasing BC production as a result. Similar results have been found in studies with G. hansenii, (Park et al 2003) and with A. xylinum ATCC 10245 (Yunoki et al 2004). In the latter report, the authors suggest that ethanol was not the carbon source for BC production and that the improvement was a consequence of ethanol suppressing the transformation of glucose in gluconic acids, a process that potentiates a more efficient polymerization of glucose into BC.…”
Section: Introductionsupporting
confidence: 90%
“…7), the addition of ethanol to the media resulted in slightly lower figures. This effect has been reported previously by Park et al (2003) and by Yunoki et al (2004). Nevertheless, these authors found an increase in BC production in the presence of ethanol from the beginning of the test, whereas in this study's tests with the addition of 1% ethanol to the culture media BC production increased only in the last part of the assay in which YE+CSL was used as the nitrogen source (Fig.…”
Section: Evaluation Of the Effect Of Ethanolsupporting
confidence: 84%
See 2 more Smart Citations
“…However, based on the literature, changes in the pH value during the cellulose synthesis process may have a very complex character and thus it is diffi cult to clearly defi ne the cause of the changes in this parameter. As an example, Yunoki et al 28 did not observe any changes in the pH for seven days of cultivation of G. xylinus ATCC 10245. Park et al 29 who cultivated the strain of G. hansenii higher than its dry weight 31, 32 .…”
Section: Resultsmentioning
confidence: 99%